Williamsburg Lives Again - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet describes the history of Colonial Williamsburg and the decision to restore the town backed by the financial support of the Rockefeller family. Discusses the important role of paint in the restoration. Includes decorated covers, a small stylized illustration, and monotone photographs throughout. The National Paint, Oil and Varnish Association, Inc., formed in 1933, was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Shellac; Paint materials; Linseed oil; Oilseeds; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint; Rockefeller family